Malignant rhabdoid tumour of the liver: A case report - Muni Varma; Gaurav Singh; Arupparna Sengupta; Shailendra Lalwani; Samarjit Singh Ghuman; Sunita Bhalla; Satish Kumar Aggarwal (Elsevier, 2021)
Malignant rhabdoid tumor (MRT) is one of very aggressive neoplasm commonly seen in kidney. An 8 months old boy presented with fever, abdominal distension, multiple vomiting and reduced oral intake. CT Angiography revealed a hyper dense mass involving multiple segments of the liver and associated rupture. He had near normal Sr. AFP (Alpha-Feto protein) levels. An emergent laparotomy revealed a tumour arising from the left lobe of liver which had ruptured already and the surface was bleeding. There was a large haemoperitoneum. A left hemi-hepatectomy was done. Post operative course was turbulent. He never recovered enough to be given chemotherapy. Prognosis was explained, the parents took the child home against medical advice. He died at home a few weeks later. Histopathological examination (HPE) revealed to be malignant rhabdoid tumour of the liver.